2008
DOI: 10.1021/bc7004329
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Linker Stability to the Activities of Anticancer Immunoconjugates

Abstract: The linker component of antibody-drug conjugates (ADC) is a key feature in developing optimized therapeutic agents that are highly active at well tolerated doses. For maximal intratumoral drug delivery, linkers are required that are highly stable in the systemic circulation, yet allow for efficient drug release at the target site. In this respect, amide bond-based technologies constitute a technological advancement, since the linker half-lives in circulation ( t 1/2 approximately 7 days) are much longer than e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
358
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 403 publications
(378 citation statements)
references
References 36 publications
(66 reference statements)
14
358
1
1
Order By: Relevance
“…In contrast, our anti-5T4 NDC had a PK that was equal to or slightly better than the WT Ab. The anti-drug ELISA also confirmed that the oxime linkage between the SMD and Ab is highly stable in vivo-a significant improvement relative to conventional maleimido linkages that have been reported to be chemically unstable in plasma (26,28).…”
Section: Nonnative Amino Acid Conjugates Demonstrate Superior In Vivosupporting
confidence: 52%
“…In contrast, our anti-5T4 NDC had a PK that was equal to or slightly better than the WT Ab. The anti-drug ELISA also confirmed that the oxime linkage between the SMD and Ab is highly stable in vivo-a significant improvement relative to conventional maleimido linkages that have been reported to be chemically unstable in plasma (26,28).…”
Section: Nonnative Amino Acid Conjugates Demonstrate Superior In Vivosupporting
confidence: 52%
“…These data are consistent with previously published studies with the other mcMMAF ADC targeting CD70. 30,31,[33][34][35] Both ADCs induced apoptosis of CD138 1 patient MM cells following 3 days' treatment, and greater dose-dependent killing was seen by J6M0-mcMMAF than J6M0-vcMMAE ( Figure 2C). Percentages of annexin V/propidium iodide (PI) cells combined were 45.8% 6 0.5% and 74.5% 6 1.2% at 0.01 mg/mL and 1 mg/mL J6M0-mcMMAF, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…A variety of forms of the ADC may be generated in vivo. For example, variants derived from ADCs, based on maleimide adducts have been described (38)(39)(40). Reactivity of ADA for all three structural components of the ADC (mAb, linker, and small-molecule drug) can be determined.…”
Section: Ada Domain Specificity Strategymentioning
confidence: 99%